Carried out at the end of learning: Perceptions of the Formative Assessment - Maya Puspitasari; Muhammad Arifin Pelawi (Indonesian Journal of Learning Education and Counseling, 2023)
Formative assessment in language learning is inevitable. The differences between formative and summative assessment do not only lie in the time when the assessment is carried out. The differences might be examined by the purposes why the assessment is conducted. This study aims to gather information about the implementation of formative assessment in the classroom. Seven open-ended questions were distributed to 100 participants in an online survey. Eighty-three responses were gathered and analysed qualitatively. The findings showed that there are different perceptions of formative assessment from formative assessment on the policy. The participants indicated that the assessment practices focused more on gaining scores than on providing positive feedback to the students. The new curriculum that emphasises more formative assessment of the pedagogy practices might fail to be implemented in the classroom.